EVALUASI PERENCANAAN STRUKTUR JEMBATAN UNDERPASS SIMPANG TUGU NGURAH RAI, BADUNG, BALI - Billy Chris Hutama Pasaribu; IGL Bagus Eratodi; Putu Ariawan; IGN Nyoman Wismantara (Jurnal Ilmiah Telsinas, 2019)
Congestion at the Tugu Ngurah Rai Roundabout junction that connects the road from Denpasar to the Nusa Dua and surrounding areas has become a problem in the city of Badung. This is because the road has not been able to handle the volume of vehicles at the intersection. Therefore it is necessary to make an underpass. The pass is planned with a total length of 408.4 meters which is divided into two parts, namely the closed section 100.40 meters and open 308 meters. The width of the road to be excavated is 16 meters wide for 2 (two) lanes. Geotechnical analysis is very necessary to plan the underpass structure, because the load that works on the underpass does not only come from traffic loads, but mostly comes from land which greatly affects structural stability. The method used for structural stability analysis in this study is the approach method based on IRC78 / 1983. The abutment design phase, like the structure of a retaining wall basically uses a trial system, then analyzes its stability provided that it must meet the value of the safety factor Sliding FS> 1.5, Bolster FS> 1.5, FS DDT> 3. In the case of the Underpass Simpang Tugu Ngurah Rai bridge the abutment is planned to be 7.8 meters high, 3.5 meters wide and 16 meters long from the ground surface. The results of the stability analysis on the abutment state that the soil can withstand shear forces, and rolling which works on the structure, but the carrying capacity of the soil cannot carry the structure above it, so the foundation below is needed. The foundation analyzed is a caissons foundation of 6 pile drill foundation with a diameter of 0.8 m and a depth of 3.4 meters. Each foundation pole can bear axial loads of 267,097 tons, so the total axial load that can be borne is 1602.55 tons. The caissons foundation with a diameter of 0.8 meters is a foundation that can withstand building structural loads on the Underpass and abutment bridges.